Hippocampal microstructural damage correlates with memory impairment in clinically isolated syndrome suggestive of multiple sclerosis. (August 2017) - Planche, Vincent; Ruet, Aurélie; Coupé, Pierrick; Lamargue-Hamel, Delphine; Deloire, Mathilde; Pereira, Bruno; Manjon, José V; Munsch, Fanny; Moscufo, Nicola; Meier, Dominik S; Guttmann, Charles RG; Dousset, Vincent; et al.
Objective: We investigated whether diffusion tensor imaging (DTI) could reveal early hippocampal damage and clinically relevant correlates of memory impairment in persons with clinically isolated syndrome (CIS) suggestive of multiple sclerosis (MS). Methods: A total of 37 persons with CIS, 32 with MS and 36 controls prospectively included from 2011 to 2014 were tested for cognitive performances and scanned with 3T-magnetic resonance imaging (MRI) to assess volumetric and DTI changes within the hippocampus, whole brain volume and T2-lesion load. Results: While there was no hippocampal atrophy in the CIS group, hippocampal fractional anisotropy (FA) was significantly decreased compared to controls. Decrease in hippocampal FA together with increased mean diffusivity (MD) was even more prominent in MS patients. In CIS, hippocampal MD was correlated with episodic verbal memory performance ( r  = −0.57, p  = 0.0002 and odds ratio (OR) = 0.058, 95% confidence interval (CI) = 0.0057–0.59, p  = 0.016 adjusted for age, gender, depression and T2-lesion load), but not with cognitive tasks unrelated to hippocampal functions. Hippocampal MD was the only variable discriminating memory-impaired from memory-preserved persons with CIS (area under the curve (AUC) = 0.77, sensitivity = 90.0%, specificity = 70.3%, positive predictive value (PPV) = 52.9%, negative predictive value (NPV) = 95.0%). Conclusion: DTI alterations within the hippocampus might reflect early neurodegenerative processes that are correlated with episodic memory performance, discriminating persons with CIS according to their memory status.